Effects of l-Tyrosine on working memory and inhibitory control are determined by DRD2 genotypes: A randomized controlled trial. (September 2016) - Colzato, Lorenza S.; Steenbergen, Laura; Sellaro, Roberta; Stock, Ann-Kathrin; Arning, Larissa; Beste, Christian
Abstract: l -Tyrosine (TYR), the precursor of dopamine (DA), has been shown to enhance facets of cognitive control in situations with high cognitive demands. However some previous outcomes were mixed: some studies reported significant improvements, while other did not. Given that TYR increases DA level in the brain, we investigated, in a double-blind, randomized, placebo-controlled design, whether the C957T genotypes of a functional synonymous polymorphism in the human dopamine D2 receptor ( DRD2 ) gene (rs6277) contribute to individual differences in the reactivity to TYR administration and whether this factor predicts the magnitude of TYR-induced performance differences on inhibiting behavioral responses in a stop-signal task and working memory (WM) updating in a N -back task. Our findings show that T/T homozygotes (i.e., individuals potentially associated with lower striatal DA level) showed larger beneficial effects of TYR supplementation than C/C homozygotes (i.e., individuals potentially associated with higher striatal DA level), suggesting that genetically determined differences in DA function may explain inter-individual differences in response to TYR supplementation. These findings reinforce the idea that genetic predisposition modulates the effect of TYR in its role as cognitive enhancer.